Energy-based motion control of a slender hull unmanned underwater vehicle. (1st August 2015) - Valentinis, Francis; Donaire, Alejandro; Perez, Tristan
Abstract: This paper presents a motion control system for tracking of attitude and speed of an underactuated slender-hull unmanned underwater vehicle. The feedback control strategy is developed using the Port-Hamiltonian theory. By shaping of the target dynamics (desired dynamic response in closed loop) with particular attention to the target mass matrix, the influence of the unactuated dynamics on the controlled system is suppressed. This results in achievable dynamics independent of stable uncontrolled states. Throughout the design, the insight of the physical phenomena involved is used to propose the desired target dynamics. Integral action is added to the system for robustness and to reject steady disturbances. This is achieved via a change of coordinates that result in input-to-state stable (ISS) target dynamics. As a final step in the design, an anti-windup scheme is implemented to account for limited actuator capacity, namely saturation. The performance of the design is demonstrated through simulation with a high-fidelity model. Abstract : Graphical abstract: Abstract : Highlights: An energy-based tracking control system is developed for an under actuated underwater vehicle. The control system, based on Port-Hamiltonian theory, controls forward speed, roll, pitch and yaw. The controller suppresses the influence of uncontrolled states on the controlled dynamics. Integral action is added through the use of a change of coordinates. An anti-windup scheme is demonstrated.